Designing and constructing mini refrigerator with thermoelectric module. Issue 1 (1st January 2022) - Tamami, F; Doyan, A; Susilawati; Hikmawati; Ayub, S; Azhar; Hudha, L S
Abstract: Cooling Engine is one application of the laws of thermodynamics. Cooling machines such as refrigerators are a necessity for everyone. Thermoelectric which has a Peltier effect can be used as an electronic component to cool objects. This research is an experimental research and the object of research is a mini-size refrigerator with thermoelectric. The purpose of this research is to analyse the performance coefficient of the mini refrigerator that has been made. The research method used is a literature study and data are taken by measuring the temperature produced from the refrigerator. The results obtained from this study are that the refrigerator can reduce the system room temperature from 28.5 °C to 13.6 13 within 10 minutes. In the next experiment with a time of one hour, the temperature in the system room was lowered to 7.7 °C. After measuring the outside temperature in the container (reservoir) and inside the refrigerator, the coefficient of performance is 0.3. The coefficient number is relatively low, because the higher the number obtained, the more efficient the refrigerator is made.